Gamelan Gong Beruk in the ritual of Ngusaba Desa in Pemaksan Bangle Temple, at Abang Districts Karangasem - Yudarta, I Gede; Garwa, I Ketut; Wardizal, Wardizal; Yulianti, Ni Ketut Dewi; Kariasa, I Nyoman (Linguistics and Culture Review, 2023)
The aims of this study to reveal the religiosity of the gamelan Gong Beruk it found in the Bangle Traditional Village, Bunutan Village Abang Districts, Karangasem Regency. This Gamelan is a traditional music ensamble it is very unique and the only one in Bali. As the Bangle peolpe’s culture creations, this gamelan has an important function to accompany the prosession and implementation of ngusaba desa ceremony in the Pemaksan Bangle Temple. There are two problems will be disscussed in this study they are How the process appearance of the gamelan Gong Beruk and how the function of it in the implementation in ngusaba desa in Pemaksan Bangle Temple. Both of these topics is very interensting because until this time the existence of gamelan Gong Beruk not widely to known by the public, and this gamelan has an important function in implementation of ngusaba desa in the Pemaksan Bangle Temple. This study is used the descriptive kualitative method where the data will be find from observation, interview, literature review and document study. The data analysis is carried out from the data collection process, reduction and conclusion.